THE COMPREHENSIVE MIDWIFERY CARE WITH NY. R IN DEPENDENT MIDWIFERY PRACTICE NURIL'S SIDOARJO - Agustin Tjondro , Lidya; Azizah, Nurul (UNIVERSITAS AIRLANGGA, 2024)
Background: The maternal mortality rate in Indonesia in 2022 will be 189 / 100 thousand live births. This figure is still high when compared to the MMR target in 2024, namely 183 / 100 thousand live births. One of the midwives' efforts to reduce MMR is by providing comprehensive/ sustainable midwifery care (CoC). The purpose of this case study is to describe the results of implementing CoC midwifery care for Mrs. R aged 29 years at TPMB Nuril Sidoarjo for 3 days. Method: This midwifery care case study uses a descriptive method, where Mrs. R is given care starting from the third trimester of pregnancy, childbirth, newborns, postpartum to family planning. CoC midwifery care provided to Mrs. R is standard midwifery care. Result: The results of the case study show that from the midwifery care given to Mrs. R, it was found that the condition of the mother and baby was still within normal limits without any complications until the end of the implementation of comprehensive midwifery care. Conclusion : The midwifery care provided to the subject was in accordance with applicable standard midwifery care procedures. So that no complications occur in the subject when midwifery care is provided.